Gonial Angle Characteristics of Class III Malocclusion in Javanese Ethnic - I Gusti Aju Wahju Ardani, - (Association of Support to Oral Health Research, 2021)
Objective: To describe the gonial angle characteristics in class III skeletal malocclusion in Javanese ethnic. Material and Methods: Pretreatment lateral cephalometric radiographs of 43 Javanese ethnic patients were measured: upper (Go1) and lower gonial angle (Go2), anterior (AFH) and posterior face height ratio (PFH), maxilla-mandibular length difference, mandibular plane angle (FMA), Y axis, ramus position, ANB angle, posterior cranial base/ramus height and mandibular body length/anterior cranial base. The relation between Go1, Go2 and other variables were analysed using correlation and regression analysis. Results: The total gonial angle is within normal range, but Go1 is below normal and Go2 is above normal. There is no difference between male and female gonial angle measurements (p=0.939 and p=0.861, respectively). Ramus position is positively correlated to Go1 (p=0.003), while AFH (p=0.000), maxilla-mandibular length difference (p=0.000), FMA (p=0.000), Y axis (p=0.000), and posterior cranial base/ramus height (p=0.018) are positively correlated to Go2. PFH is negatively correlated to Go2 (p=0.018). Conclusion: The upper gonial angle is influenced by the position of mandibular ramus, while the lower gonial angle is affected by the posterior and anterior lower facial height and mandibular size and rotation. Javanese with class III malocclusion tends to have hypodivergent facial type, with more posteriorly located mandibular ramus and excess mandibular length.